Effects of Alkoxylated Imidazoline Rust Inhibitors on the Properties of Reinforced Concrete - WANG Yaru, YANG Zhensheng, YANG Jian, LI Zhuangzhuang, SHI Nana, CHEN Long (Cailiao Baohu)
In the marine environment，reinforced concrete structures will be damaged prematurely due to chloride corrosion，and the addition of rust inhibitors can improve the performance of reinforced concrete.The rust inhibition performance of Q235 carbon steel in saturated Ca(OH)2 solution with a 3.5%NaCl mass fraction at different temperatures and additive amounts was evaluated using electrochemical polarization curves and impedance tests with alkoxylated imidazoline rust inhibitors.The effect of the rust inhibitor on the properties of reinforced concrete was also investigated through performance tests on concrete.The experimental results indicated that the rust inhibition capacity of alkoxylated imidazoline rust inhibitors increased with the temperature of the corrosion system，with the best rust inhibition effect achieved when the additive amount was 40 g/L at a test temperature of 35 ℃.Moreover， the rust inhibitor was shown to possess certain air-entraining properties， which increased the slump of concrete， reduced the setting time of cement mortar， minimized the impact on the fluidity of cement mortar， and improved the mechanical properties of concrete and its resistance to chloride ion penetration.The addition of the alkoxylated imidazoline corrosion inhibitor improved the structure and durability of the concrete.